0613 COVID-19 Is Associated with Shorter Sleep Duration among American Adults. (25th May 2022) - Narcisse, Marie-Rachelle; Bernard, Mark; Briggs, Anthony; Locklear, Clarence; Rogers, April; Sexias, Azizi; Jean-Louis, Girardin
Abstract: Introduction: The COVID-19 pandemic has deteriorated sleep health in the United States (U.S.) and worldwide. Most studies that have examined the association between COVID-19 and sleep outcomes have used a non-probability sampling with potential sampling bias and limited generalizability. We examined the association between diagnosed COVID-19 and sleep health in a large representative sample of civilian adults aged ≥18 years in the U.S. Methods: This study was based on data from the 2020 National Health Interview Survey (NHIS) of adults (n=17, 636). Sleep health was captured by self-reported sleep quantity [(very short (≤ 4 hours), short (5-6 hours), healthy (7-8 hours), or long (≥9 hours)] and sleep complaints (trouble falling and staying asleep; with responses ranging from never to every day) in the past 30 days. To account for correlated residuals among the endogenous sleep outcomes, generalized structural equation modeling (GSEM) was conducted with COVID-19 diagnosis as the predictor of interest. Other covariates (age, sex, race/ethnicity, education, employment, poverty level, marital status, birthplace, health insurance, region of residence, metropolitan areas, number of children and adults in the household, obesity, and sleep medication) were included in the models. NHIS complex probability sampling design was accounted for in descriptive and GSEM analyses. Results: About 4.2% of adults had a positive COVID-19 diagnosis. Among them, 3.1% had very short sleep, 24.2% had short sleep, 59.9% had healthy sleep, and 12.8% had long sleep; 37.0% had trouble falling some days, 10.9% most days, and 6.5% every day; and 33.7% had trouble staying asleep some days, 13.9% most days, and 6.6% every day. Findings from GSEM revealed that a history of COVID-19 almost doubled the odds of having short sleep (OR: 1.9; 95% CI: 1.1-3.4; p=0.032). No significant associations were found between COVID-19 and the other sleep outcomes. Conclusion: Individuals with a COVID-19 diagnosis were more likely to report very short sleep, although they did not exhibit a greater likelihood of reporting more sleep complaints. Further research using longitudinal national data and examining environmental factors are needed to determine causality. Support (If Any): NIH R01HL142066, R01HL095799, RO1MD004113, R01HL152453, R25HL105444